Contributions to the study of common artifacts and errors in conventional and three-dimensional radio-imaging used in the evaluation of odontal, endodontic and periodontal pathology. - Kulcsar Diana-Florina; Stoica Oana Elena; Monea Monica Dana; Stoica Alexandra Mihaela ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2020)
Introduction: X-ray radio imaging is commonly used because most diseases in the oral area can only be diagnosed by using this method. Proper identification of elements on a radiological image may also be difficult due to errors that may occur before, during or after the X-ray. These errors are called artifacts.